Virtual Counseling To Help College Students Reduce Stress During Covid-19 Pandemic - Cintami Farmawati; Nadhifatuz Zulfa; Ulviana Ulviana (Biblio Couns : Jurnal Kajian Konseling dan Pendidikan, 2022)
This research aims to determine the effect of virtual counseling in helping college students reduce stress during the COVID-19 pandemic. This research is a quantitative study using descriptive statistical methods. The research subjects were students who did virtual counseling. The data were obtained through a virtual counseling implementation questionnaire and the Perceived Strees Scale (PSS 10) instrument. Data analysis used simple regression coefficient test (t-test). The results showed that there was an effect of virtual counseling in helping students reduce stress during the COVID-19 pandemic. Meanwhile, the college student response to virtual counseling showed that 70% were very satisfied, 30% were quite satisfied and 0% were not satisfied. The effect of virtual counseling in reducing the level of stress experienced by students during the COVID-19 pandemic can be seen from the pv value of 0.000 with a percentage of 62.7%. The use of virtual counseling can be said to be effective in minimizing stress during the COVID-19 pandemic.